Persistence of Overseeded Cool-Season Grasses in Bermudagrass Turf - Thomas Serensits; Matthew Cutulle; Jeffrey F. Derr (International Journal of Agronomy)
Cool-season grass species are commonly overseeded into bermudagrass turf for winter color. When the overseeded grass persists beyond the spring; however, it becomes a weed. The ability of perennial ryegrass, Italian (annual) ryegrass, intermediate ryegrass, and hybrid bluegrass to persist in bermudagrass one year after seeding was determined. Perennial ryegrass, intermediate ryegrass, and Italian ryegrass produced acceptable ground cover in the spring after fall seeding. Hybrid bluegrass did not establish well, resulting in unacceptable cover. Perennial ryegrass generally persisted the most one year after seeding, either because of summer survival of plants or because of new germination the following fall. Plant counts one year after seeding were greater in the higher seeding rate treatment compared to the lower seeding treatment rate of perennial ryegrass, suggesting new germination had occurred. Plant counts one year after seeding plots with intermediate ryegrass or Italian ryegrass were attributed primarily to latent germination and not summer survival. Applications of foramsulfuron generally did not prevent overseeded species stand one year after seeding, supporting the conclusion of new germination. Although quality is less with intermediate ryegrass compared to perennial ryegrass, it transitions out easier than perennial ryegrass, resulting in fewer surviving plants one year later.